Autonomous and Rechargeable Microneurostimulator Endoscopically Implantable into the Submucosa - Hajer, Jan (J Vis Exp, 2018)
Gastric dysmotility can be a sign of common diseases such as longstanding diabetes mellitus. It is known that the application of high-frequency low-energetic stimulation can help to effectively moderate and alleviate the symptoms of gastric dysmotility. The goal of the research was the development of a miniature, endoscopically implantable device to a submucosal pocket. The implantable device is a fully customized electronic package which was specifically designed for the purpose of experiments in the submucosa. The device is equipped with a lithium-ion battery which can be recharged wirelessly by receiving an incident magnetic field from the charging/transmitting coil. The uplink communication is achieved in a MedRadio band at 432 MHz. The device was endoscopically inserted into the submucosal pocket of a live domestic pig used as an in vivo model, specifically in the stomach antrum. The experiment confirmed that the designed device can be implanted into the submucosa and is capable of bidirectional communication. The device can perform bipolar stimulation of muscle tissue.